Monetary regime switches in India: Policy or structure? - Michael M. Hutchison; Rajeswari Sengupta; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
We use a Markov switching model to estimate a time-varying Taylor-type rule for Indian monetary policy conduct. This empirical approach is consistent with statements of Indian monetary policy decision-makers. We find that the conduct of monetary policy over approximately the last two decades can be characterized by two regimes, which we term hawk and dove. In the first of these, policy making reveals a greater relative weight on checking inflation vis-à-vis narrowing the output gap.
Keywords: 330